Partial cation substitution reduces iodide ion transport in lead iodide perovskite solar cells. Issue 7 (23rd May 2019) - Ferdani, Dominic W.; Pering, Samuel R.; Ghosh, Dibyajyoti; Kubiak, Peter; Walker, Alison B.; Lewis, Simon E.; Johnson, Andrew L.; Baker, Peter J.; Islam, M. Saiful; Cameron, Petra J.
Abstract : Perovskite solar cells containing a mixture of A-site cations show increased activation energies for iodide diffusion. Abstract : Halide perovskite solar cells containing a mixture of A-site cations are attracting considerable interest due to their improved stability and high power conversion efficiencies. Ionic transport is known to be an important predictor of perovskite behaviour, but the impact of partial A-site substitution on iodide ion diffusion is poorly understood. Here, we combine ab initio modelling, impedance spectroscopy and muon spin relaxation to investigate the effect on iodide ion transport of incorporating a low concentration of each of seven different sized cations (from small rubidium to large guanidinium) into methylammonium lead iodide. Experimental and simulation results are in good agreement, indicating that these cation substitutions increase the activation energy for iodide ion diffusion. We show for the first time that partial guanidinium substitution into methylammonium lead iodide strongly suppresses iodide ion transport. The insights gained from this multi-technique study are important for the future design of mixed-cation perovskite solar cells with enhanced performance.